Samoa : 2019 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Samoa. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation discusses that Samoa faces several economic challenges but continues to show resilience and a high level of engagement with IMF. Growth is expected to rebound after reaching a five-year low. Price pressures driven by temporary factors are receding and inflation is projected to return to below the authorities' target of 3 percent. Samoa remains vulnerable to natural disasters and correspondent banking relationship (CBR) pressures. The authorities have made progress in implementing measures to mitigate these risks. Policies should focus on tightening fiscal policy to ensure sustainability while achieving progress towards development goals; mitigating risks from CBR pressures; improving the monetary policy transmission mechanism; and implementing structural reforms to boost potential growth and make it more inclusive. It is important to tighten fiscal policy compared to the baseline. The report also advises to introduce focused structural reforms on building resilience to natural disasters, enhancing the business environment, encouraging female labor participation, and improving the trade facilitation framework.